Disruption of sialic acid metabolism drives tumor growth by augmenting CD8+ T cell apoptosis. Issue 9 (3rd January 2019) - Cornelissen, Lenneke A.M.; Blanas, Athanasios; van der Horst, Joost C.; Kruijssen, Laura; Zaal, Anouk; O'Toole, Tom; Wiercx, Lieke; van Kooyk, Yvette; van Vliet, Sandra J.
Abstract : Sialylated glycan structures are known for their immunomodulatory capacities and their contribution to tumor immune evasion. However, the role of aberrant sialylation in colorectal cancer and the consequences of complete tumor desialylation on anti‐tumor immunity remain unstudied. Here, we report that CRISPR/Cas9‐mediated knock out of the CMAS gene, encoding a key enzyme in the sialylation pathway, in the mouse colorectal cancer MC38 cell line completely abrogated cell surface expression of sialic acids (MC38‐Sia null ) and, unexpectedly, significantly increased in vivo tumor growth compared to the control MC38‐MOCK cells. This enhanced tumor growth of MC38‐Sia null cells could be attributed to decreased CD8 + T cell frequencies in the tumor microenvironment only, as immune cell frequencies in tumor‐draining lymph nodes remained unaffected. In addition, MC38‐Sia null cells were able to induce CD8 + T cell apoptosis in an antigen‐independent manner. Moreover, low CMAS gene expression correlated with reduced recurrence‐free survival in a human colorectal cancer cohort, supporting the clinical relevance of our work. Together, these results demonstrate for the first time a detrimental effect of complete tumor desialylation on colorectal cancer tumor growth, which greatly impacts the design of novel cancer therapeutics aimed at altering the tumor glycosylation profile. Abstract : What's new? The current dogma that tumor cells express sialic acids to dampen anti‐tumor immunity has led to the development of novel therapeutic strategies aimed at dismantling sialic acid‐induced tolerance. Yet the effect of a complete loss of tumor sialylation remains to be elucidated. This study is the first to report a detrimental effect of complete tumor desialylation on colorectal cancer tumor growth, which could be attributed to augmented CD8 + T cell apoptosis. The work revisits how tumor‐associated sialic acids influence the anti‐tumor immune response and has implications for the design of novel cancer therapeutics aimed at altering the tumor glycosylation profile.